Vibrational excitation and dissociation mechanisms of CO2 under non-equilibrium discharge and post-discharge conditions. (14th July 2015) - Pietanza, L D; Colonna, G; D'Ammando, G; Laricchiuta, A; Capitelli, M
Abstract: Different mechanisms of CO2 dissociation, in discharge and post-discharge conditions, have been computed by performing a parametric numerical solution of the electron Boltzmann equation as a function of the electric field, the ionization degree and the vibrational temperatures and by considering elastic, inelastic, superelastic and electron electron collisions. Emphasis is given to the role of superelastic electronic and vibrational collisions in affecting the electron energy distribution function and relevant rates. The results show that, at low E/N values, the dissociation rates from pure vibrational mechanism can overcome the corresponding rates of electron impact dissociation. In any case, the electron impact dissociation rates are largely dependent on the transitions from excited vibrational levels.